Niobium-based oxide composite magnesium hydride hydrogen storage material and preparation method thereof
The niobium-based oxide catalyst was synthesized through hydrothermal method and calcination method, and the problem of insufficient hydrogen absorption and release performance of MgH2 hydrogen storage materials was solved, thus achieving efficient preparation of magnesium hydride hydrogen storage materials, suitable for industrial production, and improving the material Cyclic stability.
Patent Information
- Application Number
- CN202411542092.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
AI Technical Summary
The existing MgH2 hydrogen storage materials lack the kinetics and thermodynamic properties of hydrogen absorption and discharge, and the catalyst doping method has insufficient cyclic performance and industrial production problems.
Niobium-based oxide catalyst was synthesized by hydrothermal method and calcination method, and added to magnesium hydride, and the preparation temperature of the catalyst was adjusted to obtain a cube-like morphology, improving the hydrogen absorption and discharge rate and cycle stability.
It significantly improves the hydrogen absorption and discharge rate and cycle stability of magnesium hydride hydrogen storage materials, reduces costs, is suitable for large-scale industrial production, and provides good long-term circulation capabilities.
Smart Images

Figure CN119284953A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen storage materials, and in particular to a niobium-based oxide composite magnesium hydride hydrogen storage material and a preparation method thereof. Background Art
[0002] In recent years, the large-scale consumption of fossil energy has caused two serious problems: energy crisis and environmental pollution. People have gradually realized that with the continuous reduction of fossil fuel reserves, there is an urgent need to find an alternative and sustainable energy solution. In order to curb global warming and the climate deterioration it causes, the use of green and renewable energy has become crucial. Hydrogen energy, as an available energy source other than fossil energy, is regarded as an ideal substitute for fossil fuels due to its abundant reserves, efficient energy conversion rate, high energy density and clean combustion final products, and has become a potential solution to energy and environmental problems.
[0003] Magnesium hydride (MgH2) has attracted much attention due to its abundant resources, excellent reversibility and high hydrogen storage capacity of 7.6wt%. However, pure MgH2 has defects such as overly stable thermodynamic properties and poor hydrogen desorption kinetics, which limits its potential in practical applications. At present, the methods to improve the hydrogen absorption and desorption kinetics and thermodynamic properties of MgH2 mainly include catalyst doping, alloying and nano-sizing. However, alloying may have a negative impact on the capacity of hydrogen storage materials, and it is difficult to achieve fully reversible conditions; and although nano-sizing can improve performance, its complex process flow and mass production problems are difficult to overcome in the short term.
[0004] Adding catalyst is the most effective way to improve the hydrogen absorption and desorption performance of MgH2. At present, the catalyst is mainly introduced into MgH2 by ball milling. The added catalysts include transition metals, rare earth metals and their compounds, and even carbon-based materials have been used to improve MgH2. Niobium (Nb)-based materials are more commonly used catalysts, but the hydrogen storage materials currently prepared still have problems such as insufficient hydrogen absorption and desorption cycle performance. Summary of the invention
[0005] In view of the above problems, the present invention aims to provide a niobium-based oxide composite magnesium hydride hydrogen storage material and a preparation method thereof. The prepared hydrogen storage material improves the rate of hydrogen absorption and desorption and increases the stability of the hydrogen absorption and desorption cycle.
[0006] The technical solution of the present invention is as follows:
[0007] In one aspect, the present invention provides a method for preparing a niobium-based oxide composite magnesium hydride hydrogen storage material, comprising the following steps:
[0008] S1, mixing niobium powder and alkaline solution, synthesizing niobium-based oxide precursor by hydrothermal method, the reaction temperature is 180-240°C;
[0009] S2, dehydrating and decomposing the niobium-based oxide precursor by calcination, and then centrifuging, washing and drying to obtain a niobium-based oxide catalyst with a needle-like, block-like mixed morphology or a cubic morphology;
[0010] S3, adding the niobium-based oxide catalyst into magnesium hydride powder at a weight percentage of 3wt%-9wt% to obtain a niobium-based oxide composite magnesium hydride hydrogen storage material.
[0011] Preferably, in step S1, the hydrothermal method for synthesizing a niobium-based oxide precursor comprises the following steps:
[0012] 0.1-0.2 g of niobium powder was added to 30-60 mL of sodium hydroxide with a concentration of 10 mol / L and stirred to dissolve. The resulting solution was transferred to a stainless steel autoclave and heated in an oven at a reaction temperature of 200° C. for a reaction time of 6-8 h.
[0013] Preferably, in step S2, the calcination conditions of the calcination method are: heating the obtained niobium-based oxide precursor in a tube furnace for 6-8 hours at a temperature set at 500-700°C.
[0014] Preferably, in step S2, the calcined niobium-based oxide precursor is centrifuged at a centrifugal speed of 10,000 rpm, and then washed with anhydrous ethanol and deionized water for multiple times, each time for one minute, to obtain a precipitate.
[0015] Preferably, in step S2, the precipitate is dried at 60° C. for 6 hours to obtain the niobium-based oxide catalyst.
[0016] Preferably, in step S3, the ball milling adopts an omnidirectional planetary ball mill, the ball-to-material ratio is 40-50:1, the ball milling time is 10 hours, and the ball milling speed is 400 rpm.
[0017] Preferably, the cycle program of the omnidirectional planetary ball mill is set to rotate forward for 15 minutes, rest for 10 minutes, reverse for 15 minutes, and rest for 10 minutes, alternating in this mode.
[0018] Preferably, the internal environment of the omnidirectional planetary ball mill is in an argon atmosphere.
[0019] Preferably, the niobium-based oxide catalyst is added to the magnesium hydride powder in an amount of 7 wt %.
[0020] On the other hand, a niobium-based oxide composite magnesium hydride hydrogen storage material is provided, which is obtained by the preparation method of the niobium-based oxide composite magnesium hydride hydrogen storage material as described above.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention has simple operation steps for synthesizing niobium-based oxide catalysts by hydrothermal method and calcination method, and the raw materials are simple and easy to obtain. The prepared hydrogen storage material is safer to use at high temperature and has low cost; it is easy to realize industrial scale-up production and is suitable for large-scale preparation of niobium-based oxide composite magnesium hydride hydrogen storage materials.
[0023] 2. The present invention obtains a cubic niobium-based oxide catalyst by regulating the preparation temperature of the catalyst, which can significantly improve the hydrogen absorption and desorption rate of the magnesium hydride hydrogen storage material and the stability of the hydrogen absorption and desorption cycle.
[0024] 3. After ball milling with magnesium hydride, the NaNbO3 catalyst prepared in the present invention has smaller particles and larger specific surface area. - It provides a transmission channel to accelerate the diffusion of hydrogen from the MgH2 matrix to the outside, and inhibits the growth of MgH2 grains during the hydrogen absorption and desorption cycle, so that the material has a good circulation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 X-ray diffraction spectra of NaNbO3 catalysts prepared in Examples 1-4 and Comparative Example 3 of the present invention;
[0026] Figure 2 The scanning electron microscope image of the NaNbO3 catalyst prepared in Examples 1-4 of the present invention;
[0027] Figure 3 is a scanning electron microscope image of the NaNbO3 catalyst prepared in Comparative Example 3 of the present invention;
[0028] Figure 4 This is a scanning electron microscope image of the NaNbO3 catalyst prepared in Example 1 of the present invention;
[0029] Figure 5 This is an energy dispersive X-ray spectrum image of the NaNbO3 catalyst prepared in Example 1 of the present invention;
[0030] Figure 6 The hydrogen absorption curves of the samples of Inventive Examples 1-4 and Comparative Examples 1-3;
[0031] Figure 7 Dehydrogenation curves of samples of Inventive Examples 1-4 and Comparative Examples 1-3;
[0032] Figure 8 The hydrogen absorption curves of the hydrogen storage materials prepared in Example 1 and Examples 5-7 of the present invention;
[0033] Fig. 9 Dehydrogenation curves of hydrogen storage materials prepared in Example 1 and Examples 5-7 of the present invention;
[0034] Fig.10 The hydrogen storage material prepared in Example 1 of the present invention is subjected to 30 cycles of hydrogen absorption and desorption at 300°C;
[0035] Fig.11 The X-ray diffraction spectra of the hydrogen storage material prepared in Example 1 of the present invention after ball milling, dehydrogenation and rehydrogenation;
[0036] Fig.12 The figure is a flow chart for preparing a niobium-based oxide composite magnesium hydride hydrogen storage material in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the accompanying drawings and examples, but it is not intended to limit the scope of the present invention, and is only illustrative. It should be noted that, in the absence of conflict, the embodiments in the present application and the technical features in the embodiments can be combined with each other. Unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those of ordinary skill in the art to which this application belongs. The experimental methods used in the following examples are conventional methods unless otherwise specified. Materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.
[0038] Example 1
[0039] A niobium-based oxide composite magnesium hydride hydrogen storage material is prepared by the following steps:
[0040] (1) 0.2 g of niobium powder (Nb powder) was added to 30 mL of sodium hydroxide with a concentration of 10 mol / L, and the mixture was stirred and dissolved to obtain a mixed solution. The mixed solution was then transferred to a 100 ml stainless steel autoclave, and the stainless steel autoclave was placed in an oven for heating. The reaction time was 8 h and the reaction temperature was 200 ° C to obtain a Na2Nb2O6·H2O precursor.
[0041] (2) The obtained Na2Nb2O6·H2O precursor was heated in a tubular furnace at 600°C for 6 hours in an air sintering atmosphere at a heating rate of 10°C / min, and then cooled to room temperature in the furnace; then placed in a centrifuge and centrifuged at a speed of 10,000 rpm, and washed three times with anhydrous ethanol and deionized water for one minute each to obtain a precipitate, which was dried in a drying oven at 60°C for 6 hours to obtain a NaNbO3 catalyst, recorded as NaNbO3-200°C.
[0042] (3) The prepared NaNbO3 catalyst was added to MgH2 at a weight percentage of 7 wt%. In an omni-directional planetary ball mill (PMQW04), the ball milling was carried out at a speed of 400 rpm for 10 hours under an argon (Ar) environment, and the mass ratio of the added ball material was 40:1; the ball milling cycle program was set to forward rotation for 15 minutes, rest for 10 minutes, reverse rotation for 15 minutes, and rest for 10 minutes, alternating in this mode. The final product was recorded as MgH2-7wt%NaNbO3 (200°C).
[0043] Example 2
[0044] Different from Example 1, in step (1) of this example, when preparing the Na2Nb2O6·H2O precursor, the reaction temperature is 160°C, the obtained NaNbO3 catalyst is recorded as NaNbO3-160°C, and the final product is recorded as MgH2–7wt%NaNbO3(160°C).
[0045] Example 3
[0046] Different from Example 1, in step (1) of this example, when preparing the Na2Nb2O6·H2O precursor, the reaction temperature is 180°C, the obtained NaNbO3 catalyst is recorded as NaNbO3-180°C, and the final product is recorded as MgH2–7wt%NaNbO3(180°C).
[0047] Example 4
[0048] Different from Example 1, in step (1) of this example, when preparing the Na2Nb2O6·H2O precursor, the reaction temperature is 220°C, the obtained NaNbO3 catalyst is recorded as NaNbO3-220°C, and the final product is recorded as MgH2–7wt%NaNbO3(220°C).
[0049] Example 5
[0050] Different from Example 1, in step (3) of this example, the prepared NaNbO3 catalyst is added to MgH2 at a weight percentage of 5wt%, and the final product is recorded as MgH2-5wt%NaNbO3-S.
[0051] Example 6
[0052] Different from Example 1, in step (3) of this example, the prepared NaNbO3 catalyst is added to MgH2 at a weight percentage of 3wt%, and the final product is recorded as MgH2-3wt%NaNbO3-S.
[0053] Example 7
[0054] Different from Example 1, in step (3) of this example, the prepared NaNbO3 catalyst is added to MgH2 at a weight percentage of 9wt%, and the final product is recorded as MgH2-9wt%NaNbO3-S.
[0055] Comparative Example 1
[0056] The Nb2O5 catalyst was added to MgH2 at a weight percentage of 7 wt%. The milling was carried out in an omni-directional planetary ball mill (PMQW04) at a speed of 400 rpm for 10 hours under an argon (Ar) environment, with a ball-to-material mass ratio of 40:1. The milling cycle was set to rotate forward for 15 minutes, rest for 10 minutes, reverse for 15 minutes, and rest for 10 minutes, and the cycle was repeated alternately. The final product was recorded as MgH2–7wt%Nb2O5.
[0057] Comparative Example 2
[0058] Pure magnesium hydride was placed in a planetary ball mill (PMQW04) and milled at 400 rpm for 10 hours in an argon (Ar) environment, with a ball-to-material mass ratio of 40:1. The ball milling cycle was set to rotate forward for 15 minutes, rest for 10 minutes, reverse for 15 minutes, and rest for 10 minutes, and the cycle was repeated alternately. The final product was recorded as milled MgH2.
[0059] Comparative Example 3
[0060] 2.0 g Nb2O5, 20 mL ethylene glycol and 10 M NaOH solution (50 mL) were used as raw materials and stirred uniformly, and then heated in an oven at 180 ° C for 10 hours through a solvent thermal reaction to prepare a bulk NaNbO3 catalyst, and the prepared NaNbO3 catalyst was added to MgH2 at a weight percentage of 7 wt%. The prepared NaNbO3 catalyst was recorded as NaNbO3-P, and the final product was recorded as MgH2–7wt%NaNbO3-P.
[0061] Based on the above embodiments, the following experiments were conducted:
[0062] 1. X-ray diffraction experiment of NaNbO3 catalyst
[0063] The crystal structure of the NaNbO3 catalyst was determined by X-ray diffraction experiment. Taking the NaNbO3 catalysts prepared in Examples 1-4 and Comparative Example 3 as examples, the results are as follows: Figure 1 As shown. Figure 1It can be seen that the XRD images of NaNbO3 prepared at different hydrothermal temperatures in Examples 1-4 and the XRD image of the NaNbO3 catalyst prepared by the conventional method in Comparative Example 3, wherein NaNbO3 PDF#00-033-1270 represents the standard PDF card of NaNbO3. From the XRD images, it can be seen that characteristic peaks appear at 22.7°, 32.5°, 46.5°, 52.3° and 58.0°. Although the morphology of NaNbO3 at different hydrothermal temperatures is very different, the peak intensity and diffraction peak angle shown in its XRD spectrum are consistent. These results show that even under different preparation conditions, the crystal structure of NaNbO3 remains stable.
[0064] 2. SEM experiment of NaNbO3 catalyst
[0065] The microscopic morphology of the NaNbO3 catalyst was observed by scanning electron microscopy experiment, taking the NaNbO3 catalysts prepared in Examples 1-4 and Comparative Example 3 as examples. Figure 2 SEM images of NaNbO3 catalysts prepared at different hydrothermal temperatures in Examples 1-4 are shown. Specifically, Figure 2 (a) shows the SEM image of the NaNbO3 sample prepared at 160 °C hydrothermal temperature. Figure 2 (b) shows the SEM image of the sample prepared at 180 °C hydrothermal temperature; Figure 2 (c) is the SEM image of the NaNbO3 sample at 200℃ hydrothermal temperature; Figure 2 (d) is the SEM image of the NaNbO3 sample prepared at 220℃ hydrothermal temperature. Figure 2 As can be seen in (a), when the hydrothermal temperature is 160 degrees, the NaNbO3 presents a needle-like morphology, but as the temperature increases, when the hydrothermal temperature reaches 180 degrees, the nanowires begin to break and agglomerate, as shown in Figure 2 (b); however, when the hydrothermal temperature is 200 °C, its morphology is a uniform cubic shape, as shown in Figure 2 (c). However, when the temperature reaches 220 degrees, the sample morphology begins to agglomerate, as shown in Figure 2 (d) As shown. It can be determined that controlling the hydrothermal temperature can control the morphology of the sample.
[0066] Figure 3 This is a SEM image of NaNbO3 synthesized by conventional hydrothermal method in comparative example 3. Figure 3 (a) is a SEM image of NaNbO3 at 10 μm magnification; Figure 3(b) shows a SEM image of NaNbO3 at a magnification of 1 micron. The morphology of the prepared NaNbO3 shows a flake-like stacking appearance, which has obvious agglomeration and agglomeration, which is particularly obvious at the same magnification. This agglomeration phenomenon may have an adverse effect on the performance of the NaNbO3 catalyst. The disadvantage of the method for preparing the catalyst in Comparative Example 3 is that the cycle is too long and the morphology of the final product is poor.
[0067] Figure 4 This is a SEM image of the NaNbO3 catalyst prepared under 200°C hydrothermal conditions in Example 1, where Figure 4 (a) is a SEM image of NaNbO3 at 50 microns; (b) is a SEM image of NaNbO3 at 20 microns; (c) is a SEM image of NaNbO3 at 3 microns; it can be seen that the reaction is basically complete and the morphology of the sample is basically cubic;
[0068] The morphology of the catalyst has a decisive influence on its catalytic performance. By rationally designing and precisely controlling the morphology of the catalyst, its activity, selectivity and stability in various catalytic reactions can be significantly improved. Cubic catalysts usually have a higher specific surface area, which means that more active sites are exposed to the reactants, thereby improving the catalytic efficiency. Secondly, the cubic structure provides a unique geometry, which can affect the adsorption and diffusion of reactant molecules, thereby affecting the catalytic activity and selectivity. In addition, some cubic catalysts show good stability under reaction conditions, which is particularly important for long-term catalytic processes. Through the design of the cubic structure, the electronic structure of the catalyst can be regulated, thereby optimizing the adsorption and desorption of reaction intermediates and improving the catalytic activity.
[0069] The niobium-based oxide catalyst involved in the present invention exhibits the multivalent characteristics of metal ions due to the particularity of its 3d orbital electronic structure. The reduction of the valence means the enhancement of the electron transfer between the Mg-H bonds, thereby improving the adsorption performance of MgH2.
[0070] In summary, by regulating the hydrothermal temperature, a cubic NaNbO3 catalyst can be adjusted. The prepared hydrogen storage material not only shows excellent catalytic activity in the magnesium hydride solid-state hydrogen storage reaction, but also has good long-term cycle stability.
[0071] 3. Energy dispersive X-ray spectroscopy experiment of NaNbO3 catalyst
[0072] The elements in the NaNbO3 catalyst were qualitatively analyzed by energy dispersive X-ray spectroscopy experiments. Figure 5 This is the EDS image of NaNbO3. The EDS image reveals the elemental composition, among which Figure 5(a) is the EDS image of O element, Figure 5 (b) is the EDS image of Na element. Figure 5 (c) is the EDS image of the Nb element. It can be observed that each element is evenly distributed without agglomeration.
[0073] In catalyst research, firstly, the uniform distribution of elements in the EDS image usually means that the active sites in the catalyst are evenly distributed, which is very important for the effective conduct of the catalytic reaction. Each active site has the potential to participate in the reaction, thereby improving the efficiency of the catalyst and the uniformity of the reaction. Secondly, it indicates that the catalyst has good dispersion. Good dispersion helps to increase the specific surface area of the catalyst, thereby increasing the number of active sites and improving the catalytic efficiency. And the evenly distributed active components may provide better stability under the reaction conditions.
[0074] 4. Hydrogen absorption kinetics measurement experiment of different samples
[0075] The hydrogen absorption kinetics measurement experiment is used to detect the hydrogen absorption performance of the prepared samples. Taking the samples prepared in Examples 1-4 and Comparative Examples 1-3 as examples, 0.2 g of the samples prepared by ball milling are respectively placed in a customized quartz tube, and then placed in a reaction sample pool. The cells are first evacuated and the volume is calibrated. The temperature is then raised to 350 degrees and kept warm for 2 hours. The activated samples are vacuum treated, and then the adsorption kinetics of each sample is measured under the conditions of 4.5 MPaH2 and 200°C. Similarly, the desorption kinetics of the sample are measured under the conditions of 300°C and 0 MPa.
[0076] Figure 6The hydrogen absorption curves of the samples of Examples 1-4 and Comparative Examples 1-3 of the present invention at 200°C and 4.5MPa hydrogen pressure are shown in the figure. First, the NaNbO3 and MgH2 prepared at different hydrothermal temperatures were ball milled to explore the effect of NaNbO3 prepared at different hydrothermal temperatures on the hydrogen absorption performance of MgH2. The concentration ratio of the catalyst is 7wt%. It can be seen from the figure that the NaNbO3 prepared at a hydrothermal temperature of 200°C has better hydrogen absorption performance, and also exhibits excellent performance in terms of kinetics. For convenience, the NaNbO3 prepared at 200°C will be represented as NaNbO3-S in the following. It can be obtained that the composite material of MgH2–7wt%NaNbO3-S can absorb 5wt% of H2 in 12s, and 6wt% of H2 in 1.4min. Under the same time and temperature conditions, the doped Nb2O5 mentioned in Comparative Example 1 takes 13 minutes to absorb about 5wt% H2; the ball-milled magnesium hydride in Comparative Example 2 can only absorb about 5.5wt% H2 in about 40 minutes. Similarly, the sample MgH2–7wt%NaNbO3-P in Comparative Example 3 can only absorb 5.3wt% H2 in 40 minutes; in comparison, the cubic NaNbO3 prepared under 200℃ hydrothermal conditions has the best hydrogen absorption performance.
[0077] 5. Desorption kinetics measurement experiments of different samples
[0078] The desorption kinetics measurement experiment was used to detect the dehydrogenation performance of the prepared samples. Taking the samples prepared in Examples 1-4 and Comparative Examples 1-3 as examples, the desorption kinetics measurement was carried out under the conditions of 300°C and 0 MPa. Figure 7 It can be clearly seen that NaNbO3 with a hydrothermal temperature of 200°C exhibits excellent dehydrogenation performance, releasing 5wt% H2 in 6min and 7.1wt% H2 in about 1h. Under the same time and temperature conditions, after doping Nb2O5 mentioned in Comparative Example 1, it takes 9min to release about 5wt% H2; the ball-milled magnesium hydride in Comparative Example 2 can only release about 5.5wt% H2 in about 40 minutes. Similarly, MgH2–7wt% NaNbO3-P in Comparative Example 3 can only release 5wt% H2 in 6min; in contrast, the cubic NaNbO3 prepared under 200°C hydrothermal conditions has the best dehydrogenation performance. From these two charts, we can see that although the process for preparing NaNbO3 is the same, the material generated by simply changing the hydrothermal temperature has a huge impact on the hydrogen absorption and desorption performance of MgH2. Compared with NaNbO3-P prepared by the traditional hydrothermal method, the catalyst prepared by the solvent method and calcination method adopted in the present invention exhibits more superior performance.
[0079] VI. Experimental measurement of hydrogen absorption and dehydrogenation kinetics of hydrogen storage materials prepared with different catalyst concentrations
[0080] The effects of different concentrations of catalyst on the hydrogen storage material's hydrogen absorption performance were investigated by measuring the hydrogen absorption and dehydrogenation kinetics. Taking the hydrogen storage materials prepared in Example 1 and Examples 5-7 as examples, several MgH2 samples containing different amounts of NaNbO3 (MgH2-xNaNbO3-S, x=3, 5, 7, 9 wt%) were prepared to evaluate the optimal concentration of catalyst doping to achieve the best hydrogen storage performance of MgH2. The results are shown in Figure 2. Figure 8 As shown in the figure, we can see that at 200°C and 4.5MPa hydrogen pressure, the addition of 7wt% NaNbO3-S shows excellent hydrogen absorption performance, absorbing 5wt% H2 in 12s and 6wt% H2 in 85s.
[0081] like Fig. 9 As shown, at 300 °C, the dehydrogenation kinetics of MgH2-7wt%NaNbO3-S is also the fastest, releasing 5wt% of H2 in 6 min and a total of 7.1wt% of H2, proving that the optimal catalyst concentration is 7wt%.
[0082] VII. Cyclic performance test experiment of niobium-based oxide composite magnesium hydride hydrogen storage material
[0083] The cyclic performance test experiment was conducted to explore the cyclic performance of the niobium-based oxide composite magnesium hydride hydrogen storage material, taking the hydrogen storage material prepared in Example 1 as an example. The sample was subjected to hydrogen absorption at 300°C and 4.5MpaH2, and 30 cycles were tested at 300°C and 0MpaH2. Fig.10 The 30 hydrogen absorption and desorption cycle curves at 300°C for the hydrogen storage material prepared in Example 1 of the present invention. It can be seen from the figure that the hydrogen absorption amount of the sample in the first cycle reached 7wt%. After 10 cycles, the hydrogen absorption amount stabilized at 6.56wt%, which is equivalent to 93.7% of the initial hydrogen absorption amount. As the number of cycles increases, the hydrogen absorption amount further stabilizes. By the 30th cycle, the hydrogen absorption amount of the sample remained at 6.11wt%, a slight decrease compared to the 10th cycle, accounting for 93.1% of the initial hydrogen absorption amount. Based on these findings, it can be inferred that the material has good long-term cycle ability.
[0084] 8. X-ray diffraction experiment of hydrogen storage materials after ball milling, dehydrogenation and rehydrogenation
[0085] The enhancement effect of cubic NaNbO3 on the hydrogen storage performance of MgH2 was explored by X-ray diffraction experiments. Taking the hydrogen storage material prepared in Example 1 as an example, 7wt% cubic NaNbO3 was added to MgH2 and analyzed by XRD to clarify the catalytic mechanism of cubic NaNbO3. XRD analysis was performed on the MgH2-7wt% NaNbO3-S composite material after ball milling (BM), dehydrogenation (Des) and rehydrogenation (Abs).
[0086] The results are as follows Fig.11 As shown in the figure, from the curve after ball milling, we can observe that there are only MgH2 and NaNbO3. After dehydrogenation, MgH2 is converted to Mg, and the peak of NbO appears, proving that the valence state of Nb has changed, and the existence of the NaNbO3 peak confirms the stability of the additive. As for the XRD diagram after rehydrogenation, the peak matches that of MgH2 and there is no metallic Mg peak. The structural changes during the desorption-adsorption cycle are confirmed, verifying the reversibility of the reaction.
[0087] By comparing the examples and comparative examples, the preparation method of the present invention significantly improves the hydrogen absorption and desorption kinetics of magnesium hydride, reduces the thermodynamic stability, and has good cycle stability. The specific preparation method is as follows Fig.12 In particular, the NaNbO3 catalyst prepared under hydrothermal conditions at 200°C not only shows excellent catalytic activity, but also has good long-term cycle stability, making it particularly suitable for industrial-scale hydrogen storage systems.
[0088] In summary, the niobium-based magnesium hydride composite hydrogen storage system of the present invention has the ability to absorb and release hydrogen quickly. Under the conditions of 200°C and 4.5Mpa hydrogen pressure, it can absorb 5wt% of H2 within 12 seconds, 6wt% of H2 within 1.4 minutes, and 6.8wt% of H2 within 40 minutes. For pure MgH2 after ball milling, under the same experimental conditions, only 0.48wt% of H2 can be absorbed in 1 minute, and only 5.61wt% of H2 can be absorbed in 40 minutes, proving that the NaNbO3 prepared by the method does effectively improve the kinetics and thermodynamics of MgH2.
[0089] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a niobium-based oxide composite magnesium hydride hydrogen storage material, characterized in that: The following steps are involved: S1, mixing niobium powder and alkaline solution, synthesizing niobium-based oxide precursor by hydrothermal method, the reaction temperature is 180-220°C; S2, dehydrating and decomposing the niobium-based oxide precursor by calcination, and then centrifuging, washing and drying to obtain a niobium-based oxide catalyst with a needle-like, block-like mixed morphology or a cubic morphology; S3, adding the niobium-based oxide catalyst into magnesium hydride powder at a weight percentage of 3wt%-9wt%, mixing and ball milling, to obtain a niobium-based oxide composite magnesium hydride hydrogen storage material.
2. The method for preparing the niobium-based oxide composite magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step S1, the hydrothermal method for synthesizing a niobium-based oxide precursor comprises the following steps: 0.1-0.2 g of niobium powder was added to 30-60 mL of sodium hydroxide with a concentration of 10 mol / L and stirred to dissolve. The resulting solution was transferred to a stainless steel autoclave and heated in an oven at a reaction temperature of 200° C. for a reaction time of 6-8 h.
3. The method for preparing the niobium-based oxide composite magnesium hydride hydrogen storage material according to claim 2, characterized in that: In step S2, the calcination conditions of the calcination method are: heating the obtained niobium-based oxide precursor in a tube furnace for 6-8 hours at a temperature set at 500-700°C.
4. The method for preparing the niobium-based oxide composite magnesium hydride hydrogen storage material according to claim 3, characterized in that: In step S2, the calcined niobium-based oxide precursor is centrifuged at a centrifugal speed of 10,000 rpm, and then washed with anhydrous ethanol and deionized water for multiple times, each time for one minute, to obtain a precipitate.
5. The method for preparing the niobium-based oxide composite magnesium hydride hydrogen storage material according to claim 4, characterized in that: In step S2, the precipitate is dried at 60°C for 6 hours to obtain the niobium-based oxide catalyst.
6. The method for preparing the niobium-based oxide composite magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step S3, the ball milling is performed using an omnidirectional planetary ball mill, the ball-to-material ratio is 40-50:1, the ball milling time is 10 hours, and the ball milling speed is 400 rpm.
7. The method for preparing the niobium-based oxide composite magnesium hydride hydrogen storage material according to claim 6, characterized in that: The cycle program of the omnidirectional planetary ball mill is set to rotate forward for 15 minutes, rest for 10 minutes, reverse for 15 minutes, and rest for 10 minutes, and this mode is alternately carried out.
8. The method for preparing the niobium-based oxide composite magnesium hydride hydrogen storage material according to claim 7, characterized in that: The internal environment of the omnidirectional planetary ball mill is in an argon atmosphere.
9. The method for preparing the niobium-based oxide composite magnesium hydride hydrogen storage material according to claim 8, characterized in that: The niobium-based oxide catalyst was added to magnesium hydride powder at a weight percentage of 7 wt %.
10. A niobium-based oxide composite magnesium hydride hydrogen storage material, characterized in that: The material is obtained by using the preparation method of the niobium-based oxide composite magnesium hydride hydrogen storage material as described in any one of claims 1 to 9.